Assessment of health and economic benefits of walking in the Republic of North Macedonia using Health Economic Assessment Tool (HEAT) - Bukovetz, Jansun; Shuntova, Kristina; Spiroski, Igor; Memeti, Shaban (Институт за јавно здравје на Република Македонија = Institute of public health of Republic of Macedonia, 2021)
Walking as a form of physical activity has immense health benefits, but it also has economic benefits. Walking is a very efficient activity that prevents certain diseases and enables better quality of life of people who already have some disease. A considerable contribution of walking is detected in cardiovascular diseases, type 2 diabetes, obesity and chronic pulmonary diseases. The aim of this study was to make a health and economic assessment of the benefits of walking in the Republic of North Macedonia by using the Health and Economic Assessment Tool (HEAT).Materials and methods:Health Economic Assessment Tool is a relatively new tool, developed by WHO experts whose expertise is in the field of Public health and is able to calculate the health effects of regular walking and/or cycling. This study was based on using this tool for walking mode for the first time in the Republic of North Macedonia in a population group of 191 participants between the age of 20 to 73 years, with the average age of 35 years.Results:Besides the aforementioned health benefits, HEAT calculates the economic benefits of walking. The tool applied to 191 participants resulted in a total economic value of 108 808.8€ for one yearas well as reduction in mortality rate. Conclusion: We found that less than one fifth of our assessed population spends time in walking according to the WHO, CDC and AHA recommendations. The rest of them, more than four fifths are not following these recommendations. Our assessed population was relatively young, the average age being 35 years old, and the population was healthy, but still the results from this survey were not satisfying.